2012
DOI: 10.2298/jmmb101223002s
|View full text |Cite
|
Sign up to set email alerts
|

X-ray diffraction and SEM/EDX studies on technological evolution of the oxide-fluoride ceramic flux for submerged arc-surfacing

Abstract: The ceramic flux for submerged arc-surfacing with main component composition MgO (10.0 wt. %)-Al2O3 (25.0 wt. %)-SiO2 (40.0 wt. %)-CaF2 (25.0 wt. %) was prepared in a disk dryer-granulator using a sodium/potassium silicate solution as a binder. X-ray powder diffraction (XRPD) collected at r.t. identified α- phase of quartz, Al2O3, MgO and CaF2 of the initial components in the samples taken after granulation and subsequent annealing at 600 °C. In contrast to the low temperature annealing, anorthite (CaAl2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…The crucible was installed in the hot stage of the hightemperature diffractometer specially designed for studies on liquid melts [7][8]. Such set-ups, originally developed in Russia and Japan, are described in detail elsewhere [1,9]. Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The crucible was installed in the hot stage of the hightemperature diffractometer specially designed for studies on liquid melts [7][8]. Such set-ups, originally developed in Russia and Japan, are described in detail elsewhere [1,9]. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the development of new ceramic fluxes and improvement of existing ones is an actual task of modern material science. The X-ray diffraction and SEM/EDX (Scanning Electron Microscopy with Energy Dispersive X-Ray Analysis) studies of a model ceramic flux of the composition MgO (10% wt) -Al 2 O 3 (25 5 wt) -SiO 2 (40% wt) -CaF 2 (25% wt) [1], which are successfully used for welding and surfacing of various steels, have shown that after annealing at 1500 o C a complex oxide compound The CaO-Al 2 O 3 -SiO 2 oxide system is one of the most important slag compositions. Such slag is used in blast-furnace cast process as welding fluxes, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, slags based on these systems are applied in blast furnace production. Many welding fluxes and fluxes for surfacing are also known [1]. Gehlenite, anorthite, mullite, sillimanite, and other synthetic compounds of the CAS system have been used at ZAO "Technohim" (Zaporizhia, Ukraine).…”
Section: Introductionmentioning
confidence: 99%
“…Normalized background of anorthite sample in liquid and solid states at different temperatures. There are two curves at RT: before(1) and after remelting(2) …”
mentioning
confidence: 99%